Stressing factors in teachers of the educational institutions of the city of Santa Marta, in remote work modality during covid-19 - Perez-Correa, Kethy Luz
The objective of the study is to identify risk factors such as stress, deterioration and low work performance that have directly affected teachers in educational institutions in the city of Santa Marta. To collect the information, the Maslach Burnout Inventory (MBI) questionnaire was used, the frequency and intensity with which teachers suffer burnout, which corresponds to the syndrome of professional burnout. The results were divided by 3 subscales; the first assesses the experience of being emotionally exhausted by the demands of work, in which the results were 33.8% reached a low level, 22.1% obtained a medium level and 44.2% reached high levels. These results show that for teachers working all day produces work exhaustion. In the second subscale, depersonalization was evaluated where 50.6% obtained a low level, 20.1% at a medium level and 29.2% at a high level. Therefore, it is evident that half of the participants do not present attitudes of coldness and detachment. Finally, the third subscale was personal fulfillment, where 13.6% obtained a low level, 14.3% a medium level and 72.1% a high level. This means that the personal fulfillment of most teachers is high and they appreciate their job. At a general level, there is an absence of burnout in teachers.